Hukum perkawinan dalam Islam: menurut mazhab Syafi'i, Hanafi, Maliki dan Hanbali - H. Mahmud Yunus (Hidakarya Agung, 1975)
ir,c.1/ir,c.2/oen, c.3/oen,c.4/wk, c.5/oen, c.6/ir,c.7/ast c.8/wk, c.9/ir,c.10/ir,c.11-13